Optimization of the determination of total protein in biological samples and reference materials used in clinical chemistry - Lejsková, Bára, 1989-; Chromý, Vratislav, 1937-; Masarykova univerzita. Ústav chemie (2016)
Tato disertační práce se zaměřuje na stanovení celkové bílkoviny v referenčních materiálech užívaných v klinické chemii jako kalibrátory a standardy. Kjeldahlova metoda, jako metoda vhodná pro primární referenční postup, byla revidována a byly studovány dva možné postupy stanovení. Přímá analýza je založena na izolaci vysrážených bílkovin a nepřímá dvoukroková Kjeldahlova metoda stanovuje celkovou bílkovinu přes tzv. Kjeldahlův dusík korigovaný na jeho nebílkovinný dusík. Stanovení celkové bílkoviny Kjeldahlovou metodou bylo optimalizováno a byl vypracován standardní operační postup. Dále byly pozorovány a popsány změny bílkovín v referčních materiálech.
This thesis is focused on determination of total protein in reference materials used as calibrators and standards in clinical chemistry. The Kjeldahl method, as a method suitable as primary reference procedure, was reviewed and two different approaches were studied. Direct analysis made on isolated protein precipitates and an indirect two step Kjeldahl procedure determines total protein via so-called total Kjeldahl nitrogen corrected for its nonprotein nitrogen. The determination of total protein by Kjeldahl method was optimized and standard operating procedure was created. Further, changes in proteins were noticed and described in reference materials.
Vedoucí práce: Vratislav Chromý
Dizertace (Ph.D.)--Masarykova univerzita, Přírodovědecká fakulta, 2016
Keywords: bílkoviny; biuretová reakce; Kjeldahlova metoda; klinická chemie; clinical chemistry; Kjeldahl method; proteins; Biuret Reaction; disertace; dissertations